Precatio vigintiquinque linguis exarata et in Mechitaristica typographia praelo commissa inspectantibus augustissimis Ferdinando I imperatore et rege apostolico et Maria Anna imperatrice et regina post solemnem caeremoniam sacri lapidis auspicalis in novo Monasterio Mechitaristico rite peractam - (:unkn) unknown (My University, 1837)
This rare edition from the 1830s–1840s is a prayer ("Precatio") printed in 25 languages ​​at the famous Mekhitarist printing house in Vienna. The book was published to commemorate the ceremonial laying of the foundation stone ("sacri lapidis auspicalis") of the new Mekhitarist monastery in the presence of Emperor Ferdinand I and Empress Maria Anna
Vienne : [in Mechitaristica typographia], 1837. - 31 unnumbered pages ; 25 cm. - Prayer of supplication translated in 25 different languages and scripts at the occasion of the blessing and opening of the Mechitarist Monastery in Vienna and its polyglot press in 1837
Keywords: Prayers